Effect of Chemical Vapor Deposition WS2 on Viability and Differentiation of SH-SY5Y Cells - Convertino, Domenica; Mishra, Neeraj; Marchetti, Laura; Calvello, Mariantonietta; Viegi, Alessandro; Cattaneo, Antonino; Fabbri, Filippo; Coletti, Camilla (Frontiers in Neuroscience, 2020)
In recent years, transition metal dichalcogenides (TMDs) have been attracting an increasing interest in the biomedical field, thus implying the need of a deeper understanding of their impact on cell behavior. In this study we investigate tungsten disulfide (WS2) grown via chemical vapor deposition (CVD) on a transparent substrate (sapphire) as a platform for neural-like cell culture. We culture SH-SY5Y human neuroblastoma cells on WS2, using graphene, sapphire and standard culture well as controls. The quality, thickness and homogeneity of the materials is analyzed using atomic force microscopy (AFM) and Raman spectroscopy. The cytocompatibility of CVD WS2 is investigated for the first time by cell viability and differentiation assessment on SH-SY5Y cells. We find that cells differentiated on WS2, displaying a viability and neurite length comparable with the controls. These findings shine light on the possibility of using WS2 as a cytocompatible material for interfacing neural cells.